Reaming of femoral fractures with different reaming irrigator aspirator systems shows distinct effects on cardiac function after experimental polytrauma. Issue 12 (1st September 2020) - Lackner, Ina; Weber, Birte; Miclau, Theodore; Holzwarth, Nina; Baur, Meike; Gebhard, Florian; Teuben, Michel; Halvachizadeh, Sascha; Cinelli, Paolo; Pfeifer, Roman; Lipiski, Miriam; Cesarovic, Nikola; et al.
Abstract: Cardiac injuries are recorded after multiple trauma and are associated with a poor patient outcome. Reaming prior to locked intramedullary nailing is a frequently used technique to stabilize femoral diaphysis fractures. However, in polytraumatized patients, complications such as fat emboli and acute respiratory distress syndrome have been associated with reaming. The reaming irrigator aspirator (RIA) system provides concomitant irrigation and suction of the intramedullary contents, and should, therefore, reduce reaming‐associated complications. The aim of the study was to investigate cardiac function after multiple trauma with regard to two different RIA devices (RIAI vs RIAII). 15 male pigs were included in the study. Pigs received either sham treatment or multiple trauma (chest trauma, femur fracture, liver laceration, and hemorrhagic shock), followed by intramedullary nailing after reaming with either the RIAI or RIAII system (RIAII: reduced diameter of the reamer, improved control of irrigation and suction). Cardiac function was assessed by transesophageal echocardiography and systemic inflammation as well as local cardiac damage examined. Pigs of both treatment groups showed impaired cardiac function, valvular insufficiency, and cardiac damage. Systemic inflammation and local cardiac alterations were observed which might contribute to early myocardial damage in vivo. Multiple trauma including long‐bone fracture and subsequent intramedullary reaming induces cardiac dysfunction and valvular insufficiency, which might be linked to both mechanical cardiac injury and increased systemic inflammation. 6 hours after trauma there are less differences between RIAI and RIAII treatment with regard to post‐traumatic cardiac consequences in multiple injured pigs, indicating no beneficial effect of RIAII over RIAI.